International environmental governance and the Paris agreement on climate change: The adoption of the "pledge and review" governance approach - Finn Cahill-Webb (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
This paper explains the emergence of the "pledge and review" governance approach found in the Paris Agreement on Climate Change, in place of the "obligatory targets and timetables" approach found in the Kyoto Protocol, from a neo-Gramscian perspective. The main argument is that the adoption of pledge and review was a response to both the pressure to agree a new international treaty and the simultaneous divergence of interests and fragmentation of negotiation groups within the UNFCCC regime. In explaining this pressure to agree a new treaty, particular attention is given to the US and China, being the two largest emitters of greenhouse gases, looking at the key interests involved in shaping the recent move away from their long-held core negotiating positions of reluctance in accepting emission reductions. Shifts in the world political economy - the decline of US hegemony, the shift of power towards China and the East, and the emergence of a new multipolarity - and the complex nature of climate change as a problem were given as causes of fragmentation of the global climate regime. These power shifts all occur within the overarching dynamic of fossil capitalism, where the overuse of global sinks and the exploitation of natural resources remains unquestioned. Any attempt to address climate change emerges within this ideological framework of economic growth and economic development. This is continually apparent throughout the analysis, often influencing the actions of different interest groups and changes in the world political economy. When taken together, the pledge and review approach can be seen to have reinforced cooperation between nations and strengthened consensus building, facilitating the search for an agreement under differentiated interests. Being less fixed than obligatory quantitative emission reduction targets, this degree of flexibility is key to the functioning and adoption of the system. This flexibility allowed many of the key contentions within the negotiations to be sidestepped, in order for an agreement to be reached.
Keywords: F50; F53; Q54; Q58; 330; climate change; environmental governance; neo-Gramscianism; world political economy